Overexpression of the Heterochromatinization Factor BAHD1 in HEK293 Cells Differentially Reshapes the DNA Methylome on Autosomes and X Chromosome - Libertini, Emanuele; Lebreton, Alice; Lakisic, Goran; Dillies, Marie-Agnès; Beck, Stephan; Coppée, Jean-Yves; Cossart, Pascale; Bierne, Hélène (Frontiers in Genetics, 2015)
BAH domain-containing protein 1 (BAHD1) is involved in heterochromatin formation and gene repression in human cells. BAHD1 also localizes to the inactive X chromosome (Xi), but the functional significance of this targeting is unknown. So far, research on this protein has been hampered by its low endogenous abundance and its role in epigenetic regulation remains poorly explored. In this work, we used whole-genome bisulfite sequencing (BS-seq) to compare the DNA methylation profile of HEK293 cells expressing low levels of BAHD1 (HEK-CT) to that of isogenic cells stably overexpressing BAHD1 (HEK-BAHD1). We show that increasing BAHD1 levels induces de novo DNA methylation on autosomes and a marked hypomethylation on the X chromosome (chrX). We identified 91,358 regions that have different methylation patterns in HEK-BAHD1 compared to HEK-CT cells (termed “BAHD1-DMRs”), of which 83,850 mapped on autosomes and 7,508 on the X chromosome (chrX). Autosomal BAHD1-DMRs were predominantly hypermethylated and located to satellites, interspersed repeats and intergenic regions. In contrast, BAHD1-DMRs on chrX were mainly hypomethylated and located to gene bodies and enhancers. We further found that BAHD1-DMRs display a higher-order organization by being clustered within large chromosomal domains. Half of these “BAHD1-Associated differentially methylated Domains” (BADs) overlapped with lamina-associated domains (LADs). Based on these results, we propose that BAHD1-mediated heterochromatin formation is linked to DNA methylation and may play a role in the spatial architecture of the genome.